Classroom Techniques Used By The Teacher To Develop Students' English Writing Skill: A Naturalistic StudyAt Sman 1 Watumalang In 2015/2016 Academic Year - Evaolita, Vrisca; , Prof. Dr. Endang Fauziati, M. Hum; , Qanitah Masykuroh, S.S., M.Hum (2016)
This study is aimed at describing (1) classroom techniques used by the teacher in teaching English at SMAN 1 Watumalang (2) the purposes of each classroom technique (3) the students' roles (4) the teachers' roles and (5) the role of instructional material. This research is a descriptive qualitative research deploying naturalistic study approach. The data of this research are of three types namely data activities, information, and document interview script, and the data sources are event, informant, and document. The methods of collecting the data in this study are observation, interview, documentation. The results of this study show that there are some classroom techniques used by the teacher to develop students' English skill especially writing skill i.e.: image or picture, guide composition, and free writing. In addition to the classroom techniques, the teacher has roles as controller, as organizer, as prompter, as resource, as tutor, as observer and as model. Whereas, the student has roles as planner, as group, as tutor, as monitor and as evaluator. There are some materials used by the English teachers namely English textbook, and dictionary. This research concludes that the English teacher at SMAN 1 Watumalang uses various classroom techniques in teaching-learning process that can develop the students' writing skill. The various classroom techniques make the students interested and enjoy the teaching-learning of English and the students become more active and creative especially in their writing skill. This research confirms that technique image or picture in teaching narrative text, guide composition in teaching biography, and free writing in teaching exposition are significant to develop students writing skill. Moreover, the teacher's and students roles in teaching learning writing as well as the material used at SMAN 1 Watumalang are in line with with Harmer (1983) and Richard (1985: 2001) theories.